Study of the effect of plant growth regulators, size, and cultivar of the grape inflorescence explant on production of phenolic compounds in an in vitro condition - Sedighi Azam; Sedighi-dehkordi Farideh; Gholami Mansour; Rafieian-kopaei Mahmoud (Shahrekord University of Medical Sciences, 2014)
Introduction: Phenolic compounds are a large number of secondary metabolites that have useful and desirable effects in the field of agriculture, medicine, and food. This research was aimed to achieve methods of in vitro propagation of grapevine in order to apply biotechnologies for correction, growth, and optimization of products and compounds of the cultivated plant in relation to phenol ratio. Methods: In this interventional study, the effects of cultivar and size of the inflorescence explant and the gibberellin hormone in two levels, benzylaminopurine, and auxin hormones in three levels with three replicates per treatment were evaluated in relation to phenol ratio, in order to evaluate the effect of plant growth regulators, the type and size of the grape inflorescence explant on the phenol production. Results: The type of plant growth regulators affected phenolic substances production. The production of phenolic substances decreased in a medium with the highest concentration of growth regulators, 4 and 2.5 μM concentration of benzylaminopurine, and 4.9 μM of auxin. Production of phenolic substances increased in the free-plant hormone medium. In smaller samples tendency to turn brown was more regarding high amount of the sugar. Conclusion: The plant sample and the cultivar as important factors in producing phenol environment are induced by environmental stimuli like sugar, light, temperature, stress, ozone, and wound and can be actually applied to increase phenol production.